Smart biomaterials: as active immune modulators to shape pro-regenerative microenvironments - Zhang, Wenning; Zeng, Xianyi; Deng, Xikai; Yang, Fenglei; Ma, Xiaoyuan; Gao, Wei (Frontiers in Cell and Developmental Biology, 2025)
The field of smart biomaterials has evolved from passive scaffolds to dynamic, immune-modulating platforms capable of actively shaping regenerative microenvironments. This review explores the transition from inert to autonomous systems, emphasizing innovations in material responsiveness—such as pH, temperature, and enzymatic sensitivity—that enable intelligent interactions with biological cues. A key focus is the role of macrophage polarization in tissue repair, where biomaterials regulate immune responses through physicochemical properties and spatiotemporally controlled immunomodulatory factor release. Applications in cancer immunotherapy, myocardial regeneration, and scar inhibition highlight their therapeutic potential. Advances in biomimetic design and multiscale modeling accelerate rational development. However, clinical translation faces challenges in biosafety, scalability, and regulatory approval. Future directions point towards precision immune engineering, integrating optogenetic control, artificial intelligence-driven personalized design, and synergistic multimodal therapies. Ultimately, smart biomaterials are pioneering precision immune engineering, offering transformative strategies for regenerative medicine and disease intervention.